Case Report: Novel Dietary Supplementation Associated With Kidney Recovery and Reduction in Proteinuria in a Dialysis Dependent Patient Secondary to Steroid Resistant Minimal Change Disease - Gbadegesin, Rasheed A.; Hernandez, Loren P. Herrera; Brophy, Patrick D. (Frontiers in Pediatrics, 2021)
Minimal change disease (MCD) is the most common cause of nephrotic syndrome worldwide. For decades, the foundation of the treatment has been corticosteroids. However, relapse rate is high and up to 40% of patients develop frequent relapsing/steroid dependent course (1) and one third become steroid resistant. This requires treatment with repeated courses of corticosteroids, and second and third line immunomodulators increasing the incidence of drug related adverse effects. More recently, there have been reports of a very small subset of Nephrotic Syndrome (NS) patients who are initially steroid sensitive and later become secondarily steroid resistant (2). The disease course in this small subset is often protracted leading ultimately to end stage kidney disease requiring dialysis or kidney transplantation. Unfortunately, patients with this disease course do not do well post transplantation because 80% of them will develop disease recurrence that will ultimately lead to graft failure (3,4). Few approaches have been tried over many years to reduce the frequency of relapses, and steroid dependence and there is absolutely no therapeutic intervention for patients who develop secondary steroid resistance. Nonetheless, their therapeutic index is low, evidencing the need of a safer complementary treatment. Several hypotheses, including an oxidative stress-mediated mechanism, and immune dysregulation have been proposed to date to explain the underlying mechanism of Minimal Change Disease (MCD) but its specific etiology remains elusive. Here, we report a case of a 54-year-old man with steroid and cyclosporine resistant MCD. The patient rapidly progressed to end stage kidney disease requiring initiation of chronic dialysis. Intradialytic parenteral nutrition (IDPN), albumin infusion along with a proprietary dietary supplement, as part of the supportive therapy, led to kidney function recovery and complete remission of MCD without relapses.